The Kidney Transplant Self-Management Scale: Instrument Development and Psychometric Testing. (January 2023) - Chung, Shu-Yu; Bakas, Tamilyn; Rawl, Susan M.; Welch, Janet; Jones, Josette; Ellis, Rebecca; Hacker, Eileen D.
This study reports the development and psychometric testing of the Kidney Transplant Self-Management Scale (KT-SMS). The instrument development phase included the following: (a) conceptual definition, item generation, and framework; (b) face validity assessment; and (c) content validity assessment. The psychometric testing phase included the following: (a) construct validity testing; (b) internal consistency reliability testing; (c) convergent validity testing; and (d) predictive power of the KT-SMS using a cross-sectional sample of kidney transplant recipients ( N = 153). Factor analysis results supported the 16-item KT-SMS as multidimensional with five domains (medication adherence, cardiovascular risk reduction, protecting kidney, ownership, and skin cancer prevention). Internal consistency reliability for the total scale and five subscales was adequate. Convergent validity was supported as the intercorrelations of the KT-SMS total score with the five subscales were significant. The KT-SMS total score and five subscales were significantly correlated with self-efficacy for managing chronic disease, patient activation, and health-related quality of life.